SHARIA BANKING DISPUTE RESOLUTION MODEL THAT IS EFFECTIVE, EFFICIENT AND FAIR - Maskanah, Ummi; Burhanuddin, Sisca Ferawati; Zaenudin, KM Ibnu Shina; Suhartini, Siti Pujiastuti (Awang Long Law Review, 2024)
Sharia banks also target MSMEs through KUR loans, growing like mushrooms in the rain. The small loan value becomes disproportionate if a dispute is resolved through the judicial process. So what is needed by financial service providers and the public is a dispute resolution model that is effective and efficient, fair and certain. Research specifications use descriptive analytical methods, with normative and empirical juridical approaches. The data used is secondary data with data collection techniques through literature studies and field studies, then the data is analyzed using legal interpretation and construction, using qualitative juridical methods. The settlement of sharia economic disputes juridically can be resolved in two ways, namely through litigation and non-litigation. According to the results of the study, currently the KUR guarantor is PT Jamkrindo Syariah under the supervision of the OJK, in practice when there is bad credit Jamkrindo Syariah chooses a non-litigation dispute resolution model by means of deliberation and mediation off line and online based on the good faith of the parties (vide Article 55 of Law Number 21 of 2008 and Perma Number 3 of 2022), so as to fulfill a sense of justice and legal certainty, therefore there is a need for a special legal umbrella for resolving sharia economic disputes outside the Court.